Systems of psychotherapy : a transtheoretical analysis - Prochaska, James O. (Brooks/Cole Pub. Co, 1999)
This comprehensive survey of the theories of psychotherapy looks at individual systems of therapy from the systems' theories of personality to their theories of psychopathology and culminating in their theories of the therapeutic process and relationship.